Scheduling Time Analysis with Critical Path Method on the Work of Master Plan Review Consulting Services in K International Airport in West Java - dyahrini, Wien; Mulyati, Yayat; Iskandar, Yanto Rachmat; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research is based on the work of master plan review consulting services in K International Airport in West Java, conducted from February to June 2019. Project scheduling shows the relationship among activities, and the overall project identifies the relationship that must be prioritized among activities and shows realistic time estimates for each activity. CPM (Critical Path Method) assumes that the activity time is known with certainty so that only a one-time factor is needed for each activity. One of the advantages of CPM is that it is suitable for formulating, scheduling, and managing various activities in all jobs, as it provides an empirically constructed schedule. This study aims to apply the CPM method in the work of master plan review consulting services in K International Airport in West Java. The results show that scheduling using the CPM method obtained 18 weeks for implementing the master plan review consulting services in K International Airport in West Java to complete a series of work activities with a budget of Rp. 2,818,381,500. Meanwhile, the schedule planned by the executor of the master plan review consulting services in K International Airport in West Java is 20 weeks with a total budget of Rp. 3,131,535,000.